Pobreza en Brasil: progresos recientes y perspectivas - Rocha, Sonia (Revista Española de Desarrollo y Cooperación, 2023)
This article presents some empirical evidences of the decline of poverty and extreme poverty in Brazil, emphasizing its relationship with the functioning of the labor market since 1996, in particular the changes in employment and labor income that took place after 2004. The recent economic recovery will probably allow for the continuing decline of poverty; nevertheless, the shortage of qualified manpower will probably lead to increases in the returns to education, with adverse effects on income inequality.